2021
DOI: 10.3390/cancers13174328
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Chimeric RNAs in Cell Plasticity and Adaptive Evolution of Cancer Cells

Abstract: Gene fusions can give rise to somatic alterations in cancers. Fusion genes have the potential to create chimeric RNAs, which can generate the phenotypic diversity of cancer cells, and could be associated with novel molecular functions related to cancer cell survival and proliferation. The expression of chimeric RNAs in cancer cells might impact diverse cancer-related functions, including loss of apoptosis and cancer cell plasticity, and promote oncogenesis. Due to their recurrence in cancers and functional ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 103 publications
1
22
0
Order By: Relevance
“…Recent studies identified several chimeric RNAs in different cancers that are associated with oncogenesis, cancer heterogeneity, and the evolution of cancer drug resistance [ 8 , 43 ]. The appearance of chimeric RNAs in a particular cell can promote functional expansion and increase phenotypic diversity to help the cell to survive in the face of new stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies identified several chimeric RNAs in different cancers that are associated with oncogenesis, cancer heterogeneity, and the evolution of cancer drug resistance [ 8 , 43 ]. The appearance of chimeric RNAs in a particular cell can promote functional expansion and increase phenotypic diversity to help the cell to survive in the face of new stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated the functional significance of various chimeric RNAs in cancer development and other genetic abnormalities [ 2 , 3 , 4 , 5 , 6 , 7 ]. Chimeric RNAs could appear in the later stages of cancer, promoting cancer heterogeneity and drug resistance [ 8 , 9 , 10 , 11 ]. As such, chimeric RNAs have been recognized as potential biomarkers and drug targets for different cancers [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…All these different disease-specific transcripts can generate the different phenotypes, which impact the normal protein interaction networks, switch pathways and change the regulatory landscape of the cells that can drive the disease development Abbreviations ARDS, acute respiratory distress syndrome; AS, alternative splicing; aTSS, alternative transcription start site; aTTS, alternative transcription termination site; DEGs, differentially expressed genes; IFN, interferon. [11][12][13][14][15]. Viral infections can also lead to widespread alternations of cellular splicing and altered transcripts, which are significantly associated with viral pathogenesis [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Chimeric transcripts are formed by the fusion of the exon/intron from two separate genes [ 22 ]. The generation of chimeric transcripts was found to be functionally involved with the development of several diseases [ 23 , 24 ]. Further, the appearance of chimeric transcripts in the cell is thought to be associated with the generation of phenotypic plasticity that helps the cell’s survival in response to specific stress [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%